NAPman: Network-Assisted Power Management for WiFi Devices - Rozner, Eric; Navda, Vishnu; Ramjee, Ramachandran; Rayanchu, Shravan (MobiSys, 2010)
WiFi radios in smart-phones consume a significant amount of power when active. The 802.11 standard allows these devices to save power through an energy-conserving Power Save Mode (PSM). However, depending on the PSM implementation strategies used by the clients/Access Points (APs), we find through controlled experiments that competing background traffic results in one or more of the following negative consequences: a significant increase, up to 300%, in a client’s energy consumption, a decrease in wireless network capacity due to unnecessary retransmissions, and unfairness. In this paper, we propose NAPman: Network-Assisted Power Management that addresses the above issues. NAPman leverages AP virtualization and a new energy-aware fair scheduling algorithm to minimize client energy consumption and unnecessary retransmissions, while ensuring fairness among competing traffic. NAPman is incrementally deployable via software updates to the AP and does not require any changes to the 802.11 protocol or the mobile clients. Our prototype implementation improves the energy savings on a smart-phone by up to 70%under varied settings of background traffic.